Beyond Retribution: Walter Benjamin and the Case for Prospective Justice - González, María Fernanda Miranda (ETHICS IN PROGRESS, 2026)
The dominant paradigm of justice in Western thought is retributive, framed through an economic logic of debt, guilt, and proportional punishment. Retributive justice promises balance but perpetually postpones its delivery. This article argues that this deferral is not a failure but a structural feature: justice conceived as debt can never be settled in the present. This holds an analogy with Christian eschatological temporality, reproduced in secularized juridical forms. The deferral is actively maintained by what Walter Benjamin identified as “mythical violence,” that is, the foundational and preservative force of law that reduces life to administrable “mere life” and functions as a freezer of political time. Through a Benjaminian lens, the article critiques this apparatus and posits an alternative: prospective justice. Reconceived not as a future ideal but as a messianic intervention in the “now-time” [Jetztzeit], prospective justice involves the collective redistribution of agency to repair harm, the restoration of inviolable human dignity, and the use of a “divine violence” directed not at individuals but at the systemic structures of legal domination. The conclusion asserts that true justice requires a shift from inhabiting the frozen time of debt to seizing the charged possibility of the Jetztzeit.